Plasma levels of interleukin-10 and nitric oxide in response to two different desflurane anesthesia flow rates - Kalayci,Dilek (2014)
OBJECTIVE: This study investigated interleukin-10 and nitric oxide plasma levels following surgery to determine whether there is a correlation between these two variables and if different desflurane anesthesia flow rates influence nitric oxide and interleukin-10 concentrations in circulation. MATERIALS AND METHODS: Forty patients between 18 and 70 years and ASA I-II physical status who were scheduled to undergo thyroidectomy were enrolled in the study. INTERVENTIONS: Patients were allocated into two groups to receive two different desflurane anesthesia flow rates: high flow (Group HF) and low flow (Group LF). MEASUREMENTS: Blood samples were drawn at the beginning (t 0) and end (t 1) of the operation and after 24 h (t 2). Plasma interleukin-10 and nitric oxide levels were measured using an enzyme-linked-immunosorbent assay and a Griess reagents kit, respectively. Hemodynamic and respiratory parameters were assessed. RESULTS: There was no statistically significant difference between the two groups with regard to interleukin-10 levels at the times of measurement. Interleukin-10 levels were increased equally in both groups at times t 1 and t 2 compared with preoperative concentrations. For both groups, nitric oxide circulating concentrations were significantly reduced at times t 1 and t 2 compared with preoperative concentrations. However, the nitric oxide value was lower for Group HF compared to Group LF at t 2. No correlation was found between the IL-10 and nitric oxide levels. CONCLUSION: Clinical usage of two different flow anesthesia forms with desflurane may increase interleukin-10 levels both in Group HF and Group LF; nitric oxide levels circulating concentrations were significantly reduced at times t 1 and t 2 compared with preoperative concentrations; however, at 24 h postoperatively they were higher in Group LF compared to Group HF. No correlation was detected between interleukin-10 and nitric oxide levels.